Analisis Faktor-Faktor yang Berhubungan dengan Perilaku Seksual Berisiko pada Remaja - Melda Ria Tarihoran; Dyan Kunthi Nugrahaeni; Suhat Suhat; Novie E. Mauliku; Siti Nur Endah Hendayani (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Risky sexual behavior among adolescents is a public health issue influenced by various factors. This study was motivated by the serious consequences of such behavior on adolescents' physical, mental, and social health, including unintended pregnancies and sexually transmitted infections. The aim of this study was to analyze the relationship between knowledge, attitudes, exposure to reproductive health information, social life, and parenting style with risky sexual behavior among adolescents. This research employed a quantitative approach with a cross-sectional design. The sample was selected using proportional random sampling from junior and senior high school students in Sukanagara Subdistrict, Cianjur Regency, totaling 334 respondents based on the Slovin formula. Data were collected using a questionnaire and analyzed through univariate analysis, bivariate analysis using the chi-square test, and multivariate analysis using multiple logistic regression. Multivariate analysis revealed significant relationships between knowledge (p=0.019), attitudes (p=0.031), and gender (p=0.021) and risky sexual behavior. However, no significant associations were found with exposure to reproductive health information, parenting style, or social life. Knowledge was identified as the most dominant factor influencing risky sexual behavior among adolescents. It is recommended that reproductive health education for adolescents be enhanced through approaches that involve schools, families, and communities in order to reduce risky sexual behavior.